Membangun Jembatan Kesadaran Multiiman: Sebuah Proposal Visioner dari Greja Kristen Jawi Wetan - Hardiyan Triasmoroadi (Reformed Center for Religion and Society, 2023)
In the face of religious tensions within the Indonesian context, the East Java Christian Church grapples with the imperative question: